Cisplatin and 5-fluorouracil with or without epidermal growth factor receptor inhibition panitumumab for patients with non-resectable, advanced or metastatic oesophageal squamous cell cancer: a prospective, open-label, randomised phase III AIO/EORTC trial (POWER) - Markus Moehler; Annett Maderer; Peter Thuss‐Patience; Baruch Brenner; Jens Meiler; Thomas Jens Ettrich; Ralf‐Dieter Hofheinz; S. Al-Batran; Arndt Vogel; Lothar Mueller; Manfred P. Lutz; Florian Lordick; et al. (2020)
•CF is the best palliative regimen in adv. ESCC.•Panitumumab added to CF failed to improve survival.•Low sEGFR linked to better PFS. BackgroundPalliative chemotherapy of advanced oesophageal squamous cell cancer (ESCC) consists of cisplatin/5-fluorouracil (CF) to target epidermal growth factor receptor (EGFR) with panitumumab (P); chemotherapy enhanced overall survival (OS) in advanced colorectal or squamous cell head and neck cancers. With prospective serum and tumour biomarkers, we tested if P added to CF (CFP) improved OS in advanced ESCC.Patients and methodsEligible patients with confirmed ESCC that was not curatively resectable or did not qualify for definitive radiochemotherapy, were randomised 1 : 1 to receive CF [cisplatin (C) 100 mg/m2 i.v., day 1; 5-fluorouracil (F) 1000 mg/m2 i.v., days 1–4] or CF plus P (9 mg/kg, i.v., day 1, each q3-week cycle) until progressive disease or unacceptable toxicity. Safety was reviewed by the Data Safety Monitoring Board after 40, 70 and 100 patients who completed at least one cycle. After 53 enrolled patients, cisplatin was reduced from 100 mg/m2 to 80 mg/m2.ResultsThe trial was stopped early based on interim efficacy results triggered by the third safety analysis: median OS (mOS) favoured CF over CFP, regardless of cisplatin dose [hazard ratio (HR) 1.77, 95% confidence interval (CI) 1.06–2.98; P = 0.028]. In the final analysis, mOS was 10.2 versus 9.4 months for CF versus CFP, respectively (HR 1.17, 95% CI 0.79–1.75; P = 0.43). One hundred (70.4%) of 142 patients in the safety population died, 51 (51.0%) with CFP. Most deaths were related to disease progression [44/49 (90%) deaths in CF versus 34/51 (67%) deaths in CFP]; objective responses [27/73 (37.0%)] were identical. The most common serious adverse events were kidney injury [3 (4.3%) versus 7 (9.7%)], general health deterioration [5 (7.1%) versus 5 (6.9%)] and dysphagia [4 (5.7%) versus 4 (5.6%)] in CF versus CFP, respectively. There were three (4.3%) and 17 (23.6%) common terminology criteria for adverse events (CTCAE) grade 5 events in CF versus CFP, respectively. Low soluble (s)EGFR levels were associated with better progression-free survival; sEGFR was induced under CFP.ConclusionEGFR inhibition added to CF did not improve survival in unselected advanced ESCC patients. The results support further liquid biopsy studies.Trial registrationClinicalTrials.gov (NCT01627379) and EudraCT (2010-020606-15). Palliative chemotherapy of advanced oesophageal squamous cell cancer (ESCC) consists of cisplatin/5-fluorouracil (CF) to target epidermal growth factor receptor (EGFR) with panitumumab (P); chemotherapy enhanced overall survival (OS) in advanced colorectal or squamous cell head and neck cancers. With prospective serum and tumour biomarkers, we tested if P added to CF (CFP) improved OS in advanced ESCC. Eligible patients with confirmed ESCC that was not curatively resectable or did not qualify for definitive radiochemotherapy, were randomised 1 : 1 to receive CF [cisplatin (C) 100 mg/m2 i.v., day 1; 5-fluorouracil (F) 1000 mg/m2 i.v., days 1–4] or CF plus P (9 mg/kg, i.v., day 1, each q3-week cycle) until progressive disease or unacceptable toxicity. Safety was reviewed by the Data Safety Monitoring Board after 40, 70 and 100 patients who completed at least one cycle. After 53 enrolled patients, cisplatin was reduced from 100 mg/m2 to 80 mg/m2. The trial was stopped early based on interim efficacy results triggered by the third safety analysis: median OS (mOS) favoured CF over CFP, regardless of cisplatin dose [hazard ratio (HR) 1.77, 95% confidence interval (CI) 1.06–2.98; P = 0.028]. In the final analysis, mOS was 10.2 versus 9.4 months for CF versus CFP, respectively (HR 1.17, 95% CI 0.79–1.75; P = 0.43). One hundred (70.4%) of 142 patients in the safety population died, 51 (51.0%) with CFP. Most deaths were related to disease progression [44/49 (90%) deaths in CF versus 34/51 (67%) deaths in CFP]; objective responses [27/73 (37.0%)] were identical. The most common serious adverse events were kidney injury [3 (4.3%) versus 7 (9.7%)], general health deterioration [5 (7.1%) versus 5 (6.9%)] and dysphagia [4 (5.7%) versus 4 (5.6%)] in CF versus CFP, respectively. There were three (4.3%) and 17 (23.6%) common terminology criteria for adverse events (CTCAE) grade 5 events in CF versus CFP, respectively. Low soluble (s)EGFR levels were associated with better progression-free survival; sEGFR was induced under CFP. EGFR inhibition added to CF did not improve survival in unselected advanced ESCC patients. The results support further liquid biopsy studies.